2002
DOI: 10.1162/089892902317205375
|View full text |Cite
|
Sign up to set email alerts
|

Wada Testing Reveals Frontal Lateralization for the Memorization of Words and Faces

Abstract: Abstract& Neuroimaging studies have suggested that specific regions of the frontal and medial temporal cortex are engaged during memory formation. Further, there is specialization across these regions such that verbal materials appear to preferentially engage the left regions while nonverbal materials primarily engage the right regions. An open question, however, has been to what extent frontal regions contribute to successful memory formation. The present study investigates this question using a reversible le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Notably, ''deep'' encoding manipulations benefited the left hemisphere only when words were used as stimuli and benefited the right hemisphere only when unfamiliar faces were used. Similar hemispheric asymmetries in memory performance are noted during intentional memorization of verbal and nonverbal stimulus materials following lesions to left and right hemisphere brain regions (Milner, 1972) and when portions of the left and right hemisphere are anesthetized with sodium amytal (Kelley et al, 2002). Collectively, these findings suggest a hierarchy of memory formation.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, ''deep'' encoding manipulations benefited the left hemisphere only when words were used as stimuli and benefited the right hemisphere only when unfamiliar faces were used. Similar hemispheric asymmetries in memory performance are noted during intentional memorization of verbal and nonverbal stimulus materials following lesions to left and right hemisphere brain regions (Milner, 1972) and when portions of the left and right hemisphere are anesthetized with sodium amytal (Kelley et al, 2002). Collectively, these findings suggest a hierarchy of memory formation.…”
Section: Discussionmentioning
confidence: 55%
“…This functional lateralization may be related to the traditional left/right MTL memory lateralization for verbal and nonverbal material, respectively, as documented by a large body of neuropsychological (e.g., Kimura 1963;Glosser et al 1995;Bohbot et al 2000;Kelley et al 2002) and functional neuroimaging (e.g., Martin et al 1997;Kelley et al 1998;Martin 1999;O'Kane et al 2005;Weber et al 2007) evidence. For example, the left hemisphere bias for encoding object information in the present study could reflect the possibility that, although our stimuli were difficult to verbally encode, subjects may have nevertheless assigned verbal attributes to the fractals during the objects task (e.g., color, spikiness, etc.)…”
Section: Discussionmentioning
confidence: 79%
“…Superimposed upon this rostro-caudal topography are medial to lateral afferent projection gradients within both perirhinal and entorhinal cortices (Saleem and Tanaka 1996;Mohedano-Moriano et al 2007). Although functional dissociations between the medial and lateral regions of these cortical structures have yet to be demonstrated, the anatomical connectivity is suggestive of a medial to lateral functional distinction in the monkey similar to that found in rodents.In humans, both neuropsychological (e.g., Kimura 1963;Milner 1972;Glosser et al 1995;Jones-Gotman et al 1997;Bohbot et al 2000;Kelley et al 2002;Kennepohl et al 2007) and neuroimaging (e.g., Moscovitch et al 1995;Martin et al 1997;Bellgowan et al 1998;Kelley et al 1998;Sommer et al 2005) studies have documented material and process-specific distinctions in the medial temporal lobe (MTL). In contrast to the animal studies, however, these reports indicate that human MTL functional dissociations are primarily associated with differences in hemispheric laterality, with left MTL processing meaningful or linguistic information and right MTL processing spatial information.…”
mentioning
confidence: 99%
“…1 The few studies that have evaluated the issue of stimulus type reported that different types of stimulus contribute differently to the clinical preoperative questions that the IAP memory performance can address. [2][3][4] We aim to investigate the effect of using verbal stimuli versus dually encodable line drawings depicting simple objects or scenes on lesion lateralisation and side of injection, and to evaluate whether different types of memory stimulus provide different information during IAP in patients with refractory MTLE.…”
mentioning
confidence: 99%